A Training Evaluation on the Capacity Building for Open and Distance Learning Materials at Bangladesh Open University - Rashid, AQM Bazlur (Journal of Agriculture & Rural Development, 2008)
A 5 day long training programme of the teachers of BOU on the capacity building for open and distance learning materials was held during 12-15 and 19 March 2006 with a view to upgrading skill, knowledge and quality for their better educational exposure in imparting distance education. Fifty terminologies concerning ODL materials were used to evaluate the effectiveness of the training programme through pre and post evaluation. In pre-evaluation at the beginning of the training session out of 50 only 25 terminologies were assessed to be acquainted satisfactory with the participants knowledge while the rest 25 were assessed at the end of the training programme yielding significantly as much as 39% improvement on the term like ISSN followed by 27% in tele-conferencing. Based on the result, it is revealed that the training has been found effective in imparting appropriate required knowledge of technology including ODL educating materials such as writing of self learning modules, preparing scripts for radio, television, audio-video tapes, e-learning techniques, video conferencing, tele-conferencing, mediated communications etc. with the expectation that the training would have the useful impact on the teachers educating efficiency of BOU teachers. The probable definitions on the acquaintancy of terminologies used have been incorporated. Key words: Training, evaluation, capacity building, ODL.